Pogostost in vsebina poročanja o športu žensk v časopisih Delo in Slovenske novice leta 2015 - Ličen, Simon (Družboslovne razprave, 2019)
The article presents a quantitative analysis of 3,155 articles on sports published by the Delo and Slovenske Novice newspapers in 2015. The theoretical framework guiding the study includes the concepts of gatekeeping, agenda-setting and symbolic annihilation of women's sports. Women's sports receive less coverage than men's (10.4-12.5 vs. 74.9-79.4 percent). Articles on women's sports are shorter, less detailed and focus on individual sports. However, female athletes are not necessarily annihilated or consistently misrepresented. Other findings provide an insight into selected trends in sports reporting in Slovenia, including the amount of coverage dedicated to different topics and sports
Keywords: agenda-setting; Analiza vsebine; content analysis; kvantitativna analiza besedil; prednostno tematiziranje; representation of women's sports; reprezentacija športa žensk; simbolno zaničevanje; Sports for women; Sports journalism; symbolic annihilation; Športno novinarstvo; Women in journalism; Ženske v novinarstvu; Ženski športi